A compact wideband antenna with an orthogonal radiating choke for broadside gain enhancement - Chi, Lidong (2023)
A broadband compact antenna is proposed in this paper with an enhanced broadside gain performances in the +/- z directions. A design method of complementary gains is presented to overcome the gain reduction caused by the cancellation of reverse currents in the middle of the band of interest, where a design equation of the excited element of the antenna is given. This objective is achieved by accurately analyzing the resonant modes of the two parallel connected antennas of the excited element in order to achieve an overall wideband radiator. An orthogonal radiating choke (ORC) is proposed to remove the gain depression due to the leakage of electromagnetic waves toward the upper portion of the band of interest through simultaneously enhancing the broadside gain and choking the end-fire travelling wave. Each one patch of the ORC acting as both a TM10 mode microstrip antenna and a choke of end-fire travelling wave. With the help of the ORC, the gain in +/- z directions is enhanced by 13.1 dB at 6 GHz compared to that without the ORC. The proposed antenna presents a realized broadside gain of 2.1-7.8 dBi in the +/- z directions within a bandwidth of 158% (700 MHz - 6 GHz). Both the simulated and measured results demonstrate that the proposed antenna exhibits desirable bandwidth and gain characteristics and is a promising candidate for broadband integrated wireless systems.